International Normalized Ratio Targets for Left-Sided Mechanical Valve Replacement - Gupta, Saurabh; Belley-Cote, Emilie P.; Sarkaria, Anisha; Pandey, Arjun; Spence, Jessica; McClure, Graham; Panchal, Puru; Jaffer, Iqbal H.; An, Kevin; Eikelboom, John; Whitlock, Richard P. (Thrombosis and Haemostasis, 2018)
Background Guidelines recommend higher international normalized ratio (INR) targets for patients with mechanical valves believed to be at higher risk for thromboembolism. Higher INR targets are associated with increased bleeding risk. We performed a systematic review and meta-analysis assessing effects of lower and higher INR targets on thromboembolic and bleeding risk in patients with mechanical heart valves.Methods We searched Cochrane CENTRAL, MEDLINE and EMBASE for randomized controlled trials (RCTs) evaluating lower versus higher INR targets for adults with bileaflet mechanical valves. We performed title and abstract screening, full-text review, risk of bias evaluation and data collection independently and in duplicate. We pooled data using a random effects model and used the Grading of Recommendations Assessment, Development and Evaluation framework to evaluate overall quality of evidence.Results We identified six RCTs (n = 5,497). Lower INR targets were associated with significantly less bleeding—22% versus 40% (relative risk [RR]: 0.54, 95% confidence interval [CI]: 0.31, 0.93, p = 0.03, very low quality). There was no difference in thromboembolism—2% in both groups (RR: 1.28, 95% CI: 0.88, 1.85, p = 0.20, very low quality) or mortality—5.5% with lower INR targets versus 8.5% (RR: 1.00, 95% CI: 0.82, 1.21, p = 0.47, moderate quality).Conclusion In patients with mechanical valves, higher INR targets are not supported by current evidence, which is of very low quality. In fact, our systematic review suggests that lower INR targets offer significantly lower bleeding risks with no significant difference in thromboembolic risk.
Keywords: controlled trials; oral anticoagulants; thrombosis; cardiology; warfarin